ANALISIS KINERJA RUAS JALAN JARIT-PUGER JEMBER PROVINSI JAWA TIMUR - Fatimah, Irvina; Najid, Najid (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
In addition to serving as a vital link between neighborhoods for residents, roads also serve as a tool for facilitating daily activities like travel and commerce. Population has a big impact on transportation activities. The volume of traffic is also impacted by the high population density. The Jatir-Puger road in Jember, East Java, serves as one illustration. We will talk about the road performance on Jalan Jatir-Puger in Jember, East Java, in this study. MKJI or The Indonesian Highway Capacity Manual 1997 serves as the research source. To gather information about these roads, the research method employs observation. Then calculations for volume, speed, density, side resistance, and capacity will be made using the data obtained.